Improve children’s literacy with the reading aloud method - Hashina Qiamu Mumtaziah; Syifaul Fuada; Leonardi Paris Hasugian; Ellis Susmawati; Nadzifah Nadzifah; Deti Indah Kiranti; Rifa Alia Syahidah; Karynda Natalie Theofilus; Cahyo Hasanudin; Subairi Subairi; Muhathir Muhathir; Hayani Wulandari; Mahmudah Salwa Gianti (Community Empowerment, 2023)
Children who lack motivation and interest in learning and reading often demonstrate apathy and are easily discouraged, leading to a lack of concentration on their educational pursuits. As a result, these students face challenges in their academic journey. Therefore, it is crucial to make concerted efforts to enhance children's literacy by implementing the reading aloud approach, which can positively influence their overall growth and development in the Rusunawa Ciseureuh Purwakarta community. The primary objective of this program is achieved through the utilization of the reading-aloud technique. The anticipated outcomes of this program encompass increased children's motivation and interest in literacy, which will be supported by supplementary elements such as incorporating enjoyable learning techniques, engaging in gardening activities, decorating pots, and providing incentives for participating children.